Discourse as interdisciplinary connectivity: UN, political science and linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
At the present stage of development of linguistics, the focus of attention of scientists working in its various fields is the linguistic personality in all its styles and forms. The need for communicative practice aimed at its optimization and determination of factors representing the success of communication predetermined an increase in interest in discourse and its components. In addition, the attention of researchers is attracted by specific types of discourse, and in this regard, the study of official discourse is actual task. This article focuses on the discourse as an interdisciplinary connectivity of political science and linguistics identifying its specific features, as well as differences and similarities from other species through official discourse, in particular, the official discourse of the UN.